Maternal perspectives on probiotics, intake of probiotic food and occurrence of atopic dermatitis among children in selected urban communities in Laguna, Philippines - Garcia, Cherry Ann G.
Atopic dermatitis (AD), also known as eczema, is the most common chronic relapsing skin disease in children, affecting approximately 10% to 30% of children worldwide. For this reason, the research community investigated possible innovative prevention and treatment strategies for AD. One of these strategies was the manipulation of the intestinal flora through probiotics. This study is a cross-sectional, analytic study on 680 mothers and 680 children recruited in selected urban communities in Laguna, Philippines. Most mothers (92%, n=625) had highly positive attitude to probiotics. Compositescores were computed for questions on maternal attitude to probiotics, perceived behavioral control, and intention of giving probiotics to children. Path analysis was run to check for association and the resulting path showed significant association between attitude and intention, attitude and intake, behavioral control and intake, behavioral control and intention, and intention and intake of probiotic food. Female children (42.43%) have higher intake than males (30.61%). High intake was also noted among children of mothers with educational attainment of Vocational (45.45%) and College and higher (41.09%); among low- (38.92%) and middle-income families (44.06%); and among those without family history of AD (38.55%). As for the frequency of consumption of probiotic food, 3 out of 10 of the respondents reported daily intake of at least one bottle of the probiotic foods enumerated. Among 680 respondents, 18.09% (n=123) were diagnosed as having atopic dermatitis, while 81.91% (n=557) were without AD. This study showed that controlling for the effect of family history of AD, the odds of having atopic dermatitis was 2.1 times higher among those with low intake status compared to children with high intake status. Furthermore, the odds of having atopic dermatitis was 3.9 times higher among those with no intake compared to children with high intake status. With both results having a p-value of <0.0001), the association is significant. Mother?s attitude, percieved control and intention are positively associated with higher total intake among children. The intake of probiotics among children in the sample population was high. Onw out of three children consumed a probiotic drink daily. Basedon the results of this study, intake of probiotic food was a protective factor against atopic dermatitis. CHERRY ANN G. GARCIA.